Candides and Cassandras: Technology and Free Speech on the Roberts Court - Ashutosh Bhagwat (Washington University Law Review, 2018)
John Roberts assumed his position as Chief Justice of the United States just prior to the commencement of the October 2005 Term of the Supreme Court. That was seven years after Google was incorporated, one year before Facebook became available to the general public, and two years before Apple released the first iPhone. The twelve years of the Roberts Court have thus been a period of constant and radical technological innovation and change, particularly in the areas of mass communication and the media. It is therefore somewhat astonishing how few of the Roberts Court’s free speech decisions touch upon new technology and technological change. Indeed, it can be argued that only two cases directly address new technology: Brown v. Entertainment Merchants Association on video games, and Packingham v. North Carolina on social media. Packingham, it should be noted, is the only Roberts Court free speech case directly implicating the Internet. Even if one extends the definition of cases addressing technology (as I do), only four cases, at most, can be said to address technology and free speech. It seems inevitable that going forward, this is going to change. In particular, recent calls to regulate “fake news” and otherwise impose filtering obligations on search engines and social media companies will inevitably raise important and difficult First Amendment issues. Therefore, this is a good time to consider how the Roberts Court has to date reacted to technology and what that portends for the future. This paper examines the Roberts Court’s free speech/technology jurisprudence (as well as touching upon a few earlier cases), with a view to doing just that. The pattern that emerges is a fundamental dichotomy: some Justices are inclined to be Candides, and others to be Cassandras. Candide is the main character of Voltaire’s satire Candide, ou l’Optimisme, famous for repeating his teacher, Professor Pangloss’s mantra “all is for the best” in the “best of all possible worlds.” Cassandra was the daughter of King Priam and Queen Hecuba of Troy in Greek mythology, condemned by the god Apollo to accurately prophesize disaster, but never to be believed. While not all justices fit firmly within one or the other camp, the Roberts Court is clearly divided relatively evenly between technology optimists and technology pessimists. The paper begins by analyzing the key technology/free speech decisions of the Roberts Court, and classifying the current Justices as Candides or Cassandras based on their opinions or votes in those cases. In the remainder of the paper, I offer some thoughts on two obvious questions. First, why is the Court divided between Candides and Cassandras and what qualities explain the divergence (spoiler: it is not simply partisan or political preferences). And second, what does this division portend for the future. As we shall see, my views on the first issue are consistent with, and indeed closely tied to, Greg Magarian’s analysis of Managed Speech on the Roberts Court. On the second question, I am modestly (but only modestly) optimistic that the Candides will prevail and that the Court will not respond with fear to new technology. I am, in other words, hopeful that the Court will fend off heavy handed efforts to assert state control over the Internet and social media, despite the obvious threats and concerns associated with that technology. I close by considering some possible regulatory scenarios and how the Court might respond to them.
Keywords: Roberts Court; Technology and free speech; Freedom of speech; Online speech; First amendment